Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Assessment of Fellowship Didactic Curricula in Hematology/Oncology: Cross-Sectional Findings From the PODCAST-HOF Trial - Ronak H. Mistry; Karine Tawagi; Daniel J. Hausrath; Samantha A. Armstrong; Inas A. Abuali; Ankoor N. Biswas; Srijan Valasapalli; Pranali S. Pachika; Moriah K. Forster; Ericson Stoen; Yurhee Lee; Giuliana G. Berardi; et al. (Journal of Cancer Education, 2026)

The influence of cold temperature exposure on markers of bone health in humans: A scoping review - R. Allan; H.T. Hurst; B. Akin; N. Liles; J. Dickson; J. Knill-Jones; J. Sinclair; S. Dillon; S.J. Hesketh; C. Mawhinney (Journal of Thermal Biology, 2026)

Damage equivalent strain as a metric for tidal turbine blade fatigue scenario comparison - J. Dillenburger-Keenan; C. Courade; C. Dillon; H. Knoblauch; P. Cronin; C. Frost (Ocean Engineering, 2026)

Registry versus claims-based index dates for studies of cancer diagnosis in administrative data - Sarah E. Soppe; Sharon Peacock Hinton; Jamie C. Halula; Jennifer L. Lund; Chris D. Baggett; Sandi L. Pruitt; Megan A. Mullins; Ellis C. Dillon; Matthew E. Barclay; Matthew Thompson; Nicholas Pettit; Georgios Lyratzopoulos; et al. (Cancer Causes & Control, 2025)

DNA repair pathways in the mitochondria - Dillon E. King; William C. Copeland (DNA Repair, 2025)

Effects of ocean acidification on the interaction between calcifying oysters (Ostrea chilensis) and bioeroding sponges (Cliona sp.) - Imke M. Böök; Erik C. Krieger; Nicole E. Phillips; Keith P. Michael; James J. Bell; Wayne D. N. Dillon; Christopher E. Cornwall (Frontiers in Marine Science, 2024)
Ocean acidification can negatively affect a broad range of physiological processes in marine shelled molluscs. Marine bioeroding organisms could, in contrast, benefit from ocean acidification due to reduced energetic costs of bioerosion. Ocean acidification could thus exacerbate negative effects (e.g. reduced growth) of ocean acidification and shell borers on oysters. The aim of this study was to assess the impact of ocean acidification on the oyster Ostrea chilensis , the boring sponge Cliona sp., and their host-parasite relationship. We exposed three sets of organisms 1) O. chilensis , 2) Cliona sp., and 3) O. chilensis infested with Cliona sp. to pH T 8.03, 7.83, and 7.63. Reduced pH had no significant effect on calcification, respiration and clearance rate of uninfested O. chilensis . Low pH significantly reduced calcification leading to net dissolution of oyster shells at pH T 7.63 in sponge infested oysters. Net dissolution was likely caused by increased bioerosion by Cliona sp. at pH T 7.63. Additionally, declining pH and sponge infestation had a significant negative antagonistic effect (less negative than predicted additively) on clearance rate. This interaction suggests that sponge infested oysters increase clearance rates to cope with higher energy demand of increased shell repair resulting from higher boring activity of Cliona sp. at low seawater pH. O. chilensis body condition was unaffected by sponge infestation, pH, and the interaction of the two. The reduction in calcification rate suggests sponge infestation and ocean acidification together would exacerbate direct (reduced growth) and indirect (e.g., increased predation) negative effects on oyster health and survival. Our results indicate that ocean acidification by the end of the century could have severe consequences for marine molluscs with boring organisms.

Transcriptomic and developmental effects of persistent organic pollutants in sentinel fishes collected near an arctic formerly used defense site - Renee Jordan-Ward; Frank A. von Hippel; Maria Eugenia Sancho Santos; Catherine A. Wilson; Zyled Rodriguez Maldonado; Danielle Dillon; Tom Titus; Alison Gardell; Amina Salamova; John H. Postlethwait; Elise Contreras; Staci L. Capozzi; et al. (Environmental Pollution, 2024)

Physiologically-informed predictions of climate warming effects on native and non-native populations of blue catfish - Vaskar Nepal; Maggie Dillon; Mary C. Fabrizio; Troy D. Tuckey (Journal of Thermal Biology, 2024)

Differential gene expression and developmental pathologies associated with persistent organic pollutants in sentinel fish in Troutman Lake, Sivuqaq, Alaska - Renee Jordan-Ward; Frank A. von Hippel; Catherine A. Wilson; Zyled Rodriguez Maldonado; Danielle Dillon; Elise Contreras; Alison Gardell; Michael R. Minicozzi; Tom Titus; Bobby Ungwiluk; Pamela Miller; David Carpenter; et al. (Environmental Pollution, 2024)

Honey bee foraging density depends on plant size - T. Macallan Penberthy; Moira K. Dillon; Xingyao Chen; Matina C. Donaldson-Matasci (Animal Behaviour, 2023)

Metabolomes of bumble bees reared in common garden conditions suggest constitutive differences in energy and toxin metabolism across populations - Ellen C. Keaveny; Mitchell R. Helling; Franco Basile; James P. Strange; Jeffrey D. Lozier; Michael E. Dillon (Journal of Insect Physiology, 2023)

High variability and exceptionally low thermal conductivities in nearshore sediments: a case study from the Eckernförde Bay - Regina Usbeck; M. Dillon; N. Kaul; A. Lohrberg; F. Nehring; A. C. Ploetz (Marine Geophysical Research, 2023)
Heat flow measurements are a standard technique in Geophysics both onshore and offshore. Recently, such measurements became increasingly important in shallow waters. The increasing amount of offshore power installations makes it necessary to have a good knowledge about the subsurface heat flow and the thermal properties of the sediments to optimize the construction of the necessary powerlines. While the thermal properties are well studied for deep ocean sediments, only few published data exist for nearshore sediments. In this study, we investigate the sediment temperatures and thermal conductivities of nearshore sediments in the German part of the Baltic Sea. The shallow sediment temperatures reflect the interplay of the response to the seasonal cycle in connection with the sediments’ thermal conductivity. We find thermal conductivity values ranging from 0.67 to 3.34 W/(m*K) for the sediments down to ~ 4.2 m below seafloor. This variability exceeds that of conservative estimates widely used for coastal sediments and is also much higher than the variability found in the deep oceans. Sandy sediments show thermal conductivities larger than 1 W/(m*K) whereas organic-rich muds have lower values (< 1 W/(m*K)). Furthermore, the thermal conductivities seem to decrease with increasing free gas content in the sediment. The latter needs to be confirmed by further investigations.

A novel method for extraction and quantification of feather triiodothyronine (T3) and application to ecotoxicology of Purple Martin (Progne subis) - Jonathan M. Branco; Erika Hingst-Zaher; Danielle Dillon; Renee Jordan-Ward; Joe Siegrist; Jason D. Fischer; Luis Schiesari; Frank A. von Hippel; C. Loren Buck (Environmental Pollution, 2023)

Effects of elevated water temperature on cutthroat trout angler catch rates and catch‐and‐release mortality in Idaho streams - Kevin A. Meyer; Joshua L. McCormick; Joseph R. Kozfkay; Jeff C. Dillon (Fisheries Management and Ecology, 2023)
The concern is growing that angling may need to cease at elevated summer water temperatures to protect salmonid populations. Cutthroat Trout Oncorhynchus clarkii in streams were caught, marked and released using artificial dry flies at temperatures from 13.5 to 25.7°C to evaluate whether subsequent recapture with backpack electrofishing (an index of relative survival) was reduced when the water temperature was elevated at the time of landing, and to evaluate the effect of water temperature on angler catch rates. The electrofishing recapture rate of marked fish (i.e. relative survival) declined as water temperature increased, from 0.58 for fish landed at 23°C. However, angler catch declined similarly as water temperature increased, from 5.2 fish/h at 23°C. After accounting for both declines, fish mortality/angler might be higher at cooler water temperatures than at warmer temperatures. Therefore, inhibiting fishing at elevated water temperatures may not benefit trout populations any more than at cooler temperatures.

Mapping ancient sedimentary organic matter molecular structure at nanoscales using optical photothermal infrared spectroscopy - Aaron M. Jubb; M. Rebecca Stokes; Ryan J. McAleer; Paul C. Hackley; Eoghan Dillon; Jing Qu (Organic Geochemistry, 2023)

Antibacterial activity of metal–phenanthroline complexes against multidrug-resistant Irish clinical isolates: a whole genome sequencing approach - Megan O’Shaughnessy; Jasmine Hurley; Shane C. Dillon; Celine Herra; Pauraic McCarron; Malachy McCann; Michael Devereux; Orla Howe (JBIC Journal of Biological Inorganic Chemistry, 2022)

Effectiveness of Interventions to Improve Oral Cancer Knowledge: a Systematic Review - Nikhil A. Ahuja; Satish K. Kedia; Kenneth D. Ward; Latrice C. Pichon; Weiyu Chen; Patrick J. Dillon; Hitesh Navaparia (Journal of Cancer Education, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Seasonal changes in steroid and thyroid hormone content in shed skins of the tegu lizard Salvator merianae - Lucas A. Zena; Danielle Dillon; Kathleen E. Hunt; Carlos A. Navas; Kênia C. Bícego; C. Loren Buck (Journal of Comparative Physiology B, 2022)

A combination of an antioxidant with a prebiotic exerts greater efficacy than either as a monotherapy on cognitive improvement in castrated-obese male rats - Titikorn Chunchai; Puntarik Keawtep; Apiwan Arinno; Napatsorn Saiyasit; Dillon Prus; Nattayaporn Apaijai; Wasana Pratchayasakul; Nipon Chattipakorn; Siriporn C. Chattipakorn (Metabolic Brain Disease, 2020)

Hydrologic and cost benefit analysis at local scale of streambed recharge structures in Rajasthan (India) and their value for securing irrigation water supplies - Y. Dashora; P. Dillon; B. Maheshwari; P. Soni; H. K. Mittal; R. Dashora; P. K. Singh; R. C. Purohit; P. Katara (Hydrogeology Journal, 2019)

The Pacific Meridional Mode over the last millennium - Sara C. Sanchez; Dillon J. Amaya; Arthur J. Miller; Shang-Ping Xie; Christopher D. Charles (Climate Dynamics, 2019)

Unrecognized and imperilled diversity in an endemic barb (Smiliogastrini, Enteromius ) from the Fouta Djallon highlands - Ray C. Schmidt; Megan N. Dillon; Natalie M. Kuhn; Henry L. Bart; Frank Pezold (Zoologica Scripta, 2019)
The Upper Guinean Forests of Guinea, Sierra Leone and Liberia contain high levels of freshwater biodiversity. The Guinean Range and associated Fouta Djallon highlands separate two biogeographical provinces in the region and served as a refugium during past climatic fluctuations. While many species of freshwater fishes are restricted to one biogeographical province or the other, some are reported to occur on both sides of the divide. Here, we examine the molecular and morphological diversity of an endemic small African barb, Enteromius foutensis , reported to occur in both provinces. This integrative analysis revealed unrecognized diversity and suggests recent, or ongoing, events that facilitated geodispersal and subsequent divergence in the region. The molecular analysis revealed three divergent and well‐supported populations within E. foutensis . Accounting for allometric shape variation allowed us to observe diagnostic morphological differences among the populations. Enteromius foutensis sensu stricto is restricted to the Little Scarcies drainage in Guinea and northern Sierra Leone. Our study revealed two candidate species distinct from E. foutensis . One is likely a narrow endemic restricted to a small area in the Konkouré River basin; the other candidate species inhabits the upper Senegal and Gambie River drainages. How these patterns of diversity compare with other freshwater species from the Fouta Djallon highlands and the conservation status of these candidate species are also discussed.

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

A simple method using farmers’ measurements applied to estimate check dam recharge in Rajasthan, India - Y. Dashora; P. Dillon; B. Maheshwari; P. Soni; R. Dashora; S. Davande; R. C. Purohit; H. K. Mittal (Sustainable Water Resources Management, 2018)

Bisphenol A induces DSB-ATM-p53 signaling leading to cell cycle arrest, senescence, autophagy, stress response, and estrogen release in human fetal lung fibroblasts - Laziyan Mahemuti; Qixuan Chen; Melanie C. Coughlan; Cunye Qiao; Nikolai L. Chepelev; Maria Florian; Dillon Dong; Robert G. Woodworth; Jin Yan; Xu-liang Cao; Kylie A. Scoggan; Xiaolei Jin; et al. (Archives of Toxicology, 2018)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

The economic and environmental impacts of precision agriculture and interactions with agro-environmental policy - J. Schieffer; C. Dillon (Precision Agriculture, 2015)

Integrating Satellite Imagery with Simulation Modeling to Improve Burn Severity Mapping - Eva C. Karau; Pamela G. Sikkink; Robert E. Keane; Gregory K. Dillon (Environmental Management, 2014)

Spatio-temporal variation in invasion of woodlands and forest by Phytophthora cinnamomi - B. L. Shearer; C. E. Crane; R. G. Fairman; M. J. Dillon; R. M. Buehrig (Australasian Plant Pathology, 2014)

A novel role for antibiotic resistance plasmids in facilitating S almonella adaptation to non‐host environments - Sonia Paytubi; Sonia Aznar; Cristina Madrid; Carlos Balsalobre; Shane C. Dillon; Charles J. Dorman; Antonio Juárez (Environmental Microbiology, 2014)
Summary It is believed that the main role of plasmids that encode multiple antibiotic resistance is to confer their hosts the ability to survive in the presence of antimicrobial compounds. In the pathogenic bacterium S almonella , plasmids of the incompatibility group HI 1 account for a significant proportion of antibiotic resistance phenotypes. In this work, we show that plasmid R 27 has a strong impact on the global transcriptome of S almonella T yphimurium strain SL 1344 when cells grow at low temperature and enter the stationary phase. Down‐regulated genes include pathogenicity islands, anaerobic respiration and metabolism determinants. Up‐regulated genes include factors involved in the response to nutrient starvation, antimicrobial resistance, iron metabolism and the heat shock response. Accordingly, cells harbouring R 27 are more resistant to heat shock than plasmid‐free cells. The use of a different IncHI1 plasmid, pHCM1 , provided evidence that these plasmids facilitate adaptation of S almonella to environmental conditions outside their host(s). This is consistent with the fact that conjugative transfer of IncHI1 plasmids only occurs at low temperature. A significant number of the R 27‐dependent alterations in gene expression could be correlated with expression of a plasmid‐encoded orthologue of the global modulator H ‐ NS , which is up‐regulated when cells grow at low temperature.

The impact of seawater saturation state and bicarbonate ion concentration on calcification by new recruits of two Atlantic corals - S. J. de Putron; D. C. McCorkle; A. L. Cohen; A. B. Dillon (Coral Reefs, 2011)

Development of a codominant CAPS marker linked to PRSV-P resistance in highland papaya - S. Dillon; C. Ramage; S. Ashmore; R. A. Drew (Theoretical and Applied Genetics, 2006)

Diversity of locust gut bacteria protects against pathogen invasion - R. J. Dillon; C. T. Vennard; A. Buckling; A. K. Charnley (Ecology Letters, 2005)
Diversity–invasibility relationships were explored in the novel context of the colonization resistance provided by gut bacteria of the desert locust Schistocerca gregaria against pathogenic bacteria. Germ‐free insects were associated with various combinations of one to three species of locust gut bacteria and then fed an inoculum of the pathogenic bacterium Serratia marcescens . There was a significant negative relationship between the resulting density of Serratia marcescens and the number of symbiotic gut bacterial species present. Likewise there was a significant inverse relationship between community diversity and the proportion of locusts that harboured Serratia . Host mortality was not negatively correlated with resistance to gut‐invasion by Serratia marcescens , although there were significantly more deaths among pathogen fed germ‐free insects than tri‐associated gnotobiotes. The outcome is consistent with the predictions of community ecology theory that species‐rich communities are more resistant to invasion than species‐poor communities.

Genetic mapping of a PRSV-P resistance gene in “highland papaya” based on inheritance of RAF markers - S. Dillon; C. Ramage; R. Drew; S. Ashmore (Euphytica, 2005)

Sea-floor methane blow-out and global firestorm at the K–T boundary - M. D. Max; W. P. Dillon; C. Nishimura; B. G. Hurdle (Geo-Marine Letters, 1998)

Genetic structuring among Alaskan Pacific herring populations identified using microsatellite variation - M. O'Connell; M. C. Dillon; J. M. Wright; P. Bentzen; S. Merkouris; J. Seeb (Journal of Fish Biology, 1998)
Five highly variable microsatellite loci were used to investigate population structuring in Pacific herring Clupea pallasi collected from Kodiak Island, two sites in the Bering Sea and four sites within Prince William Sound, Alaska. All loci revealed high levels of variability with heterozygosity estimates ranging from 86 to 97% (mean heterozygosity: 89%). The variation was structured significantly among sites suggesting that the samples investigated were genetically distinct from each other. Genetic divergence was greatest between populations from the Bering Sea and those from Prince William Sound. The Kodiak Island and Point Chalmers samples appeared to be distinct from the Prince William Sound and Bering Sea populations. The observed genetic distance relationships among samples could be explained largely in terms of geographical separation.